Godfatherism and political party financing in Nigeria: analysing the 2015 general election - Sule, Babayo; Mohd Azizuddin Mohd Sani,; Bakri Mat, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Godfatherism is one of the major obstacles towards genuine democratisation and good governance in Nigeria. In every political setting, there are financiers of politicians for elective positions and the financed ones. In Nigeria, the phenomenon of godfatherism denotes multi-billionaires sponsoring anointed candidates for elections at all levels in return for favours and undue advantage towards the sponsors. This is a problem which impedes the emergence of popular and credible candidates who can deliver the dividends of democracy. The work examined the role played by godfathers in sponsoring politicians during the 2015 General Elections including the nature and dimension of the financing as well as its effects on the outcome of elections. The paper used a qualitative method of data collection and analysis where interview was conducted with some selected informants from various categories involving politicians, party stakeholders, academicians and focus group discussion with some selected electorates. The primary data obtained was analysed using qualitative method with existing secondary data on the subject of study. The study discovered that, godfatherism played a vital role in determining candidates for the major parties and that, a new dimension in godfatherism emerged where politicians who control power now transformed into financiers of their elections unlike before. The study recommends that, for a better selection of candidates and transparency in fielding contestants for elections, party primary elections should be transparent and INEC as the electoral body responsible for election conduct in Nigeria should intensify measures of checkmating money politics and fostering of candidates selection based on party principles and not anointment.